Spine radiosurgery - Gerszten, Peter C.; Ryu, Samuel (Thieme Medical Publishers, Inc, 2015)
Written by leading experts from the fields of neurosurgery, radiation oncology, and medical physics, this book is the definitive reference for clinical applications of state-of-the-art radiosurgery of the spine. It discusses the benefits as well as the limitations of current spine radiosurgery treatments